The Effect of Work Family Conflict on the Performance of Female Employees in the Population and Civil Registration Office of Deli Serdang Regency in 2019 - Hazura Mutia (Junal Ilmu Manajemen, 2020)
This study aims to determine the effect of work family conflict on performance on female employees of the Department of Population and Civil Registration in Deli Serdang Regency. The population in this study were 39 female employees of the Population and Civil Registry Office of Deli Serdang Regency and the sample was taken with a purposive sampling technique so that the number of samples was 34 people. Data obtained by distributing questionnaires to respondents then the data is processed with SPSS version 22.0 for windows. The data analysis technique used is a simple linear regression test with the formula Y = a + bX + e. Simple linear regression test results obtained by the equation Y = 11.965 + 0.938X where work family conflict has a positive influence on performance variables. T test results for X against Y with 6,723> 2,037, thus H0 is accepted because tcount> t table so that work family conflict has a significant effect on performance. R value of variables X and Y of 0.765 means that the relationship between work family conflict and performance is 76.5%, meaning that there is a high relationship between variables.